Aproveitamento de resíduos da Cooperativa de Agricultores Familiares de Paragominas para elaboração de produtos alimentares para a merenda escolar - ARAÚJO, Mariza Lima de (2019)
Family farming represented by the Cooperative of Small Rural Producers of Uraim and Condomínio Rural - COOPERURAIM has great relevance in the municipality of Paragominas, since it is responsible for the supply of fruits, vegetables, vegetables and fruit pulps in this municipality and nearby. The present study aimed to evaluate the production scenario of COOPERURAIM that serves school meals in the city of Paragominas, the acceptability of products based on agro-industrial residues that were previously discarded, in addition to evaluating the products formulated from these residues for the purpose to generate income and work for producers and analyze the needs of customers in relation to these new products. This study is a qualitative, exploratory and documentary research with the application of semi-structured questionnaires, in addition to the training of cooperative members in Good Food Handling Practices and the application of a culinary workshop with all the products formulated so that they are perfectly prepared by the cooperative members. To verify acceptability and consumer satisfaction, these products were subjected to the Acceptability Test and the Kano method.As a result found, it is observed that COOPERURAIM still needs to diversify its production, improve the work performed and reduce waste of waste. In order to reduce these residues, some preparations were formulated, among them: ―wheat flour cake with roasted and crushed pumpkin seed. Through the Acceptance Test and Kano Method, it is concluded that all preparations were satisfactory to consumers, that is, they can be inserted in school meals and in the market as a source of income for farmers.